Geochemical signature and origin of natural gas in the Weixinan Depression, Beibu Gulf Basin, South China Sea - Jiajun Qu; Lin Wei; Chunzhen Li; Dujie Hou; Desheng Hu; Yong Man (Natural Gas Industry B)
The Weixinan Depression is a petroliferous depression in the Beibu Gulf Basin. After years of related research, scholars have gained a certain understanding of the oil accumulation law in the depression. In recent years, some gas reservoirs with thicknesses of 14–84 m have been found in this area, showing good exploration prospects for natural gases. However, there are few studies on the geochemical characteristics and origin of natural gases in the depression, which significantly hinders gas exploration. There are three sets of source rocks in the Liushagang Formation: upper, middle, and lower source rocks (SR1, SR2, and SR3). The crude oils are divided into three groups based on geochemical indicators such as carbon isotope, C30 4-methylsterane index (4-MSI), and Pr/Ph. Group I oils exhibit relatively low carbon isotope and 4-MSI values, Group II oils exhibit relatively low carbon isotope and moderate 4-MSI values, and Group III oils show relatively heavy carbon isotope values. By comparing the gas components, light hydrocarbons, and carbon isotope characteristics of the Weixinan natural gases, it was found that the gases are generally wet and are oil-type gases, with the main difference being maturity. Based on maturity, the natural gases can be divided into highly mature and mature gases. For oil–source and gas–source correlation, the Group I and II oils are considered to be derived from SR1, and the Group Ⅲ oils and natural gases are considered to be derived from SR3.